Comparative reinfection rate of one-stage versus two-stage revision in the management of periprosthetic joint infection following total hip arthroplasty: a meta-analysis - Yueying Qin; Zeshou Liu; Liwen Li; Yuxing Yang; Xiaomeng Huang; Weiming Liang; Longbao Lin (BMC Musculoskeletal Disorders)
Abstract Background Debates persist on the optimal surgical approach for treating Periprosthetic joint infection (PJI) following total hip arthroplasty (THA). This meta-analysis aimed to compare the reinfection rate of one-stage revision versus two-stage revision for PJI after THA. Methods A comprehensive search was performed in four databases (PubMed, Embase, Web of Science, and Cochrane Library) to locate articles that assessed the reinfection rate of one-stage revision compared to two-stage revision. Meta-analyses of reinfection rate were performed. Results A total of 14 articles including of 1429 patients were chosen for inclusion in this meta-analysis, with 561 patients in the one-stage group and 868 patients in the two-stage group. The meta-analysis of the 14 trials revealed that there was no statistically significant disparity in the reinfection rate between the two groups(OR = 1.34, 95% CI 0.92 ~ 1.93, P = 0.12, I2 = 0). A subgroup analysis was conducted based on the presence of a well-defined algorithm for decision making in either a one-stage or two-stage revision. There was no statistically significant difference in reinfection rate between one-stage and two-stage revision if there was a decision algorithm(OR = 0.83, 95% CI 0.44 ~ 1.54, P = 0.55, I2 = 0). If not, the reinfection rate of one-stage revision was significantly higher than that of two-stage revision(OR = 1.79, 95% CI 1.11 ~ 2.88, P = 0.02, I2 = 0). Postoperative hip function score was significantly better in the one-stage revision group than that of the two-stage revision group(SMD = 0.54, 95% CI 0.31 ~ 0.78, P<0.05, I2 = 79%). Conclusions A strategy that is clearly defined and can be used for decision making in one-stage or two-stage revision is necessary for the treatment of PJI after THA. When there is significant damage to the soft tissue and/or the presence of strong microorganisms, a two-stage revision is recommended in order to decrease the reinfection rate. One-stage revision is recommended for patients with low-toxic infections and intact soft tissue. Trial registration PROSPERO (CRD42023450842, 17 August 2023) https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023450842 .